ANALISIS PENGGUNAAN MODEL EKSISTENSIAL DALAM PENDAMPINGAN PASTORAL DI PANTI ASUHAN ZARFAT HKI TIGA BALATA TAHUN 2017 - Deswana H Sinambela (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2018)
Abstract, This research aims describe how caregivers use existential models in pastoral care and identity the factors that support and that inhibit caregivers from pastoral care of esistensial models of children in zarfat orphanages. In this research using qualitative descriptive research method, where the technique of collecting interview data and observation so as to dig deeper about the use of model eksustensial in pastoral care. sources of data obtained in this study are two caregivers and fostor children who numbered 8 people who are sitting i junior high school SMA\SMK. The results of the analysis show that the use of existential medels in pastoral care has been done well by caregivers but there are still many foster children who can not account for every option they choose in develeping their own exitence. this tsudy conclludes that the existential model approach in pastoral care is a form of caring patterm that caregivers do in developing childrens self identity, so that children can compete in the middle of society